SETD5 Gene Haploinsufficiency in Three Patients With Suspected KBG Syndrome - Crippa, Milena; Bestetti, Ilaria; Maitz, Silvia; Weiss, Karin; Spano, Alice; Masciadri, Maura; Smithson, Sarah; Larizza, Lidia; Low, Karen; Cohen, Lior; Finelli, Palma (Frontiers in Neurology, 2020)
Mendelian disorders of the epigenetic machinery (MDEMs), also named chromatin modifying disorders, are a broad group of neurodevelopmental disorders, caused by mutations in functionally related chromatin genes. Mental retardation autosomal dominant 23 (MRD23) syndrome, due to SETD5 gene mutations, falls into this group of disorders. KBG syndrome, caused by ANKRD11 gene haploinsufficiency, is a chromatin related syndrome not formally belonging to this category. We performed high resolution array CGH and trio-based WES on three molecularly unsolved patients with an initial KBGS clinical diagnosis. A de novo deletion of 116 kb partially involving SETD5 and two de novo frameshift variants in SETD5 were identified in the patients. The clinical re-evaluation of the patients was consistent with the molecular findings, though still compatible with KBGS due to overlapping phenotypic features of KBGS and MRD23. Careful detailed expert phenotyping ascertained some facial and physical features that were consistent with MRD23 rather than KBGS. Our results provide further examples that loss-of-function pathogenic variants in genes encoding factors shaping the epigenetic landscape lead to a wide phenotypic range with significant clinical overlap. We recommend that clinicians consider SETD5 gene haploinsufficiency in the differential diagnosis of KBGS. Due to overlap of clinical features careful and detailed phenotyping is important and a large gene panel approach is recommended in the diagnostic workup of patients with a clinical suspicion of KBGS.